Modernization of Land Revenue Systems and Its Role in Enhancing Agricultural Efficiency - Hanumanthaiah M. (ಅಕ್ಷರಸೂರ್ಯ (AKSHARASURYA), 2025)
The agricultural sector continues to serve as the backbone of most developing economies, particularly in India, where a substantial portion of the population depends on farming for livelihood and sustenance. Among the numerous factors influencing agricultural productivity, the efficiency of land management stands out as crucial, and this efficiency is closely tied to the effectiveness of land revenue systems. Historically, traditional land revenue structures in India were bureaucratic, time-consuming, and vulnerable to manipulation and inaccuracies, often resulting in disputes, inefficiencies, and stagnation in rural development. In recent years, however, significant transformations have occurred with the modernization of land administration. The adoption of digitization, GIS-based land mapping, e-governance tools, and transparent digital record systems has markedly enhanced accuracy, accessibility, and accountability in land management. These technological innovations have not only streamlined administrative processes but have also empowered farmers by simplifying access to ownership records, credit facilities, and government schemes. This study examines the historical evolution of land revenue systems in India, assesses the impact of modern digital interventions on agricultural efficiency, and evaluates relevant policy initiatives aimed at promoting sustainable rural development. By analyzing both historical trends and contemporary reforms, the paper highlights how the integration of technology in land governance has led to improved land utilization, increased farmer productivity, and enhanced transparency in revenue collection. Ultimately, the research underscores that modernized land revenue administration—anchored in digitization, transparency, and efficient policy execution—serves as a vital instrument for advancing agricultural development and strengthening the rural economy.